Performance analysis of hybrid SCM/OSCDM system using the Khazani-Syed (KS) code - Sahbudin, Ratna Kalos Zakiah; Abdullah, Mohamad Khazani (World Scientific and Engineering Academy and Society, 2008)
This paper proposes a hybrid subcarrier multiplexing/optical spectrum code division multiplexing (SCM/OSCDM) system for the purpose of combining the advantages of both techniques. Optical spectrum code division multiple access (OSCDMA) is one of the multiplexing techniques that is becoming popular because of the flexibility in the allocation of channels, ability to operate asynchronously, enhanced privacy and increased capacity in bursty nature networks. On the other hand, subcarrier multiplexing (SCM) technique is able to enhance the channel data rate of OSCDMA systems. The system utilizes a new unified code construction named KS (Khazani-Syed) code based on the Double Weight (DW) and Modified Double Weight(MDW) codes. This paper also presents a new detection technique called Spectral Direct Decoding (SDD) detection technique for the OSCDM. SDD is effective in rejecting the unwanted signals that interfere with the wanted signals. This results in reduced receiver complexity and improved the performance of the hybrid system significantly.